Potential treatment of biodegradable organic matter in wastewater from wet market using Agro-Based Mixed Culture (ABMC) - Sharifuddin, Syazrin Syima (2013)
Wastewater from wet market is mainly composed of suspended solids, high levels of organic pollutants, fats, oil, and grease and often being classified as „high strength‟. This wastewater must be treated in a manner that minimizes potential harm to public health and detrimental impacts on the environment. The conventional technologies require high cost. Increasing volumes of wastewater combined with limited space availability and tightening environmental standards has promoted the development of biotechnological processes for the treatment of wastewater. A laboratory-scaled shake-flask systems experiment was conducted to test the potential of using Agro-Based Mixed Culture (ABMC) to treat biodegradable organic matter in wastewater from wet market. Different variables were tested for 13 days treatment optimization including: types of agro-base material, mixture, concentration (%v/v) and agitation (rpm). The results were subsequently compared with wastewater sample without adding ABMC as the control. All water quality parameters analyzed showed significant difference (improving water quality) compared to untreated sample (P<0.01). Treatment for all parameters tested were highest using non-sterile ABMC.50% ABMC mixture, 100% ABMC concentration, 150 rpm agitation speed for 13 days. Highest percentage reduction of water quality parameter can best be observed for Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) with 86% and 63%, respectively, followed by Ammoniacal Nitrogen (AN) with 55% reduction. Dissolved Oxygen (DO) and turbidity gives only 36% improvement and 44% reduction. The pH turns acidic from 6.10 to 5.24. Optimized ABMC treats better than Commercial EM. A larger scale and long-term treatment was tested using suspended growth batch bioreactor for 31 days treatment. At day 13, treatment performance for all parameter was better in bioreactor as compared to shake-flask system. However, by prolonging the treatment time, treatment efficiency for DO and turbidity reduced. For BOD, COD and AN, the value became constant after certain period of time. The reduction of BOD, COD and AN achieved was up to 91%, 72% and 62%, respectively. DO improve only by 14% while turbidity reduction was 48%. This study indicated that ABMC has potential to treat biodegradable organic matter in wastewater from wet market. The application of ABMC in wastewater treatment is capable of being a cost-effective biological treatment method because it is from local agricultural product which is cheap and easy to obtain.